2012
DOI: 10.1021/cb300108c
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-Specific Histone Demethylase 1 Inhibitors Control Breast Cancer Proliferation in ERα-Dependent and -Independent Manners

Abstract: Lysine specific demethylase 1 (LSD1, also known as KDM1) is a histone modifying enzyme that regulates the expression of many genes important in cancer progression and proliferation. It is present in various transcriptional complexes including those containing the estrogen receptor (ER). Indeed, inhibition of LSD1 activity and or expression has been shown to attenuate estrogen signaling in breast cancer cells in vitro implicating this protein in the pathogenesis of cancer. Herein we describe experiments that ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 42 publications
4
60
0
1
Order By: Relevance
“…Meanwhile, the addition of methoxy, fluoro or trifluoromethyl groups to the phenyl ring of tranylcypromine is known to boost LSD1 inhibition. 14,19,24 We found that introduction of these substituents restored the ability to significantly inhibit LSD in the fluorinated analogues 7g, 9a, 9c, 9d and 10d. Finally, tranylcypromine analogues containing the Cl, NO 2 or SF 5 substituents are undisclosed as LSD1 inhibitors in the literature.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Meanwhile, the addition of methoxy, fluoro or trifluoromethyl groups to the phenyl ring of tranylcypromine is known to boost LSD1 inhibition. 14,19,24 We found that introduction of these substituents restored the ability to significantly inhibit LSD in the fluorinated analogues 7g, 9a, 9c, 9d and 10d. Finally, tranylcypromine analogues containing the Cl, NO 2 or SF 5 substituents are undisclosed as LSD1 inhibitors in the literature.…”
mentioning
confidence: 75%
“…Meanwhile, as tranylcypromine itself is relatively modest in LSD1 inhibition (IC 50 ~ 25 µM), medicinal chemistry efforts have focused on second-generation analogues with higher potency. [8][9][10][11][12][13][14][15][16][17][18][19][20] Despite the mechanistic similarity between amine oxidases, the structure-activity relationships among tranylcypromine analogues is distinct for MAOs versus LSD1. For example, we found that a cyclopropylamine bearing an alkoxy substituent in lieu of the aromatic ring in 1 was a nanomolar MAO inhibitor but inactive against LSD1.…”
mentioning
confidence: 99%
“…KDM1A was also found to be highly expressed in ER-negative breast cancers [57,59,64]. Molecular knockdown of KDM1A (but not KDM1B) expression or KDM1A inhibition using TCP derivatives in MCF-7 and MDA-MB-231 cells potently inhibited proliferation and abrogated estrogen-liganded ER recruitment to promoters of some estrogen-responsive genes while leaving others unaffected ( Figure 2B) [73]. Furthermore, combinatorial therapy of anti-estrogens with KDM1A inhibitors showed a significantly better therapeutic effect compared with single endocrine therapy in terms of cell growth inhibition.…”
Section: Kdm1a In Solid Tumorsmentioning
confidence: 95%
“…On the other hand, AR was reported to recruit KDM1A at suppressor elements and block transcription androgen synthesis genes [67]. In breast cancer, KDM1A was shown to be involved in the activation of ER-targeted genes [73]. Furthermore, KDM1A, in breast cancer cells, can bind SNAIL1, ZNF217 or ZNF198 and repress gene expression of Cdh1, thus inducing EMT and migration [16,17,20,75].…”
Section: Kdm1a In Hematopoiesis and In Hematological Cancersmentioning
confidence: 99%
“…Nevertheless, reduced cell numbers have been observed upon LSD1 knockout in breast cancer cells after extended incubation times comparable to colony formation assays. 87 Since apoptosis and cell arrest are not specific readouts for a specific enzyme, off-target effects cannot be discriminated from target engagement effect in MTS assays, especially when high compound concentrations are applied. It is not clear yet if all types of Jumonji-demethylase inhibitors reduce proliferation of all cell types.…”
Section: Mts Assay (Celltiter 96mentioning
confidence: 99%